The landscape of neutralizing antibodies against SARS-CoV-2 variants: Insights from a stratified vaccination cohort - Fialho, Maria Julia; Silva, Carlos José Ferreira da; Miranda, Gabriel Brendo Alves; Assis, Izadora Sthephanie da Silva; Moreno, Adalgiza Mafra; Moura, Paulo Henrique; da Fonseca, Ana Carolina Proença; Silva, Tamara; Cardozo, Sergian Vianna (Frontiers in Immunology, 2025)
BackgroundThe COVID-19 pandemic has highlighted the crucial role of vaccines in preventing infection and reducing disease severity. However, emerging SARS-CoV-2 variants have posed challenges to vaccine-induced immunity.ObjectiveTo evaluate the immunological response and clinical characteristics of individuals with complete and incomplete COVID-19 vaccination schedules, with a focus on neutralizing antibody levels against SARS-CoV-2 variants.MethodsA total of 245 participants were analyzed and stratified by complete and incomplete vaccination status. The complete vaccination was defined by 3 doses for <40 years or 4 doses for >40 years. Clinical data, serological responses, and neutralization levels against the Wuhan strain and the Delta and Omicron (BA.1, BA.2, BA.5) variants were evaluated.ResultsAmong the participants, 71 (29%) had an incomplete vaccination schedule, and 174 (71%) had completed the recommended doses. Despite only 118 (48.2%) of participants reporting a prior positive COVID-19 test, 210 (85.7%) tested positive for anti-nucleocapsid antibodies, underscoring a high rate of undiagnosed or asymptomatic infections. Neutralization levels were reduced in incompletely vaccinated individuals, especially against the Omicron BA.2 variant (89%). A moderate-to-strong correlation was found between declining immunity and increasing time since last vaccination or infection. Older participants demonstrated lower neutralization rates against the Wuhan and Delta strains, and cross-reactivity was observed between Wuhan and Delta (r ≈ 0.7), as well as between Omicron BA.1 and BA.2. Finally, a strong negative association was observed between time since the last known SARS-CoV-2 infection and neutralization against Omicron BA.2, as well as moderate-to-strong negative correlations with Omicron BA.5 and BA.1.ConclusionCOVID-19 vaccination is effective in eliciting protective immunity, although immune evasion by recent Omicron subvariants and waning immunity over time remain challenges. These findings support the need for updated booster strategies and continued public health efforts to ensure full vaccine coverage and long-term protection.